Зрада королю чи законне право на виступ? (Козацьке повстання першої половини 1648 року у сприйнятті Вйська Запорозького) - Степанков, В. (Соціум. Альманах соціальної історії, 2006)
The article addresses the problem of the leaders of the Zaporozhian Host proving the legitimacy of the revolutionary outburst of 1648. Attention is paid to the Cossacks' increasing social and political awareness during 1630s, realizing there rights as knights and gaining functions of the «political nation». The author contradicts attempts at depicting the Cossacks as a military society, identical to mercenaries with all their wicked traits. The author supports the idea of all the participants of the outburst regarding their actions as fully legitimate, as they were not only defending their class privileges, but also the rights and freedoms the King granted the Ruthenian nation and the Orthodox Church.